To Build a Fire and other stories - London, Jack (Washington, D. C. : Library of Congress, 2005)
Jack London's To Build a Fire and Other Stories is one of the most famous stories of survival in the wilderness. Included in this collection are stories of Yukon and Alaska from 100 years ago filled with colorful characters and adventures thet show London's love of life, of people, and adventure.
La obra de Jack London para construir un fuego y otras historias es una de las historias más famosas de supervivencia en el desierto. En esta colección se incluyen historias de Yukon y Alaska de hace 100 años llenas de personajes coloridos y aventuras.
Keywords: NORTH AMERICAN LITERATURE -- NOVEL; LITERATURA NORTEAMERICANA -- NOVELA